(untitled) (Clinics, 2023)
Introduction: Glycemic control is important to avoid diabetes complications in individuals with cancer. There is no evidence for HbA1c and fructosamine as reliable biomarkers in these conditions. There are particularities in caring for patients with diabetes and cancer that can alter these biomarkers. Objective: The aim of this study was to evaluate HbA1c and fructosamine as glycemic biomarkers in people with type 2 diabetes and cancer, undergoing clinical or surgical oncological treatment. Methods: The authors conducted a single-center, retrospective analysis with people who have cancer and diabetes. Comparison of glycemic biomarkers (HbA1c, fructosamine, and Self-Monitoring of Blood Glucose [SMBG]) was performed including evaluation in individuals undergoing chemotherapy, using glucocorticoids, with anemia, hypoproteinemia or with reduced estimated Glomerular Filtration Rate (eGFR). Results: There was a strong positive correlation between fructosamine and HbA1c (n = 318, r = 0.66, p < 0.001) in people with diabetes and cancer even in those under chemotherapy (n = 101, r = 0.61, p < 0.001) or using glucocorticoids (n = 96, r = 0.67, p<0.001). There was a strong correlation between HbA1c and fructosamine in subjects with anemia (n = 111, r = 0.66, p < 0.001), hypoproteinemia (n = 54, r = 0.67, p < 0.001), or with eGFR ≥ 60 mL/min/1.73 m2 (n = 189, r = 0.70, p < 0.001), and moderate correlation with hypoalbuminemia (n = 21, r = 0.54, p = 0.001) and with reduced eGFR (n = 67, r = 0.57, p < 0.001). The correlations between fructosamine and HbA1c with SMBG were moderate (n = 164, r = 0.49, p < 0.001; n = 111, r = 0.55, p < 0.001, respectively), strong in subjects undergoing chemotherapy, with hypoalbuminemia or hypoproteinemia, and at least moderate, if eGFR < 60 mL/min/1.73 m2 or with anemia. Conclusions: Fructosamine and HbA1c can be used as glycemic biomarkers in people with diabetes and cancer, even in those with anemia, hypoproteinemia, or undergoing chemotherapy.